PENINGKATAN HASIL BELAJAR SISWA KELAS V SD MELALUI PENGGUNAAN METODE EKSPERIMEN PADA MATERI SIKLUS AIR - Rini Septianingtias (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
The Problem that is the focus of the study is the passive learning conditions of students because the teacher explains the material using the old style. The purpose of the study in this study was to describe the improvement in learning outcomes of 5th grade students at Elementary School through the use of experimental methods in water cycle material. This study uses classroom action research. Action research consists of four stages, namely planning, action, observation, and reflection. The research conducted a type of collaborative action research, meaning that the research carried out the research action with help of the observer, namely the 5th grade teacher at Elementary School. Data collection techniques in the study used four types of techniques, namely interviews, observation, field notes, and tests. As for the results of the implementation of learning using the expeimental method has increased from cycle I to cycle II. Student learning outcames have increased from pretest by 37,8% to cycle I by 62,2% and in cycle II shows completeness of 92%.